Pertanggungjawaban Hukum atas Praktik Jual Beli Unit Rumah Susun Sederhana Sewa (Rusunawa) - Prahendadmoko, Christina Maria (Magister Kenotariatan Universitas Surabaya, 2024)
The state is responsible for protecting the entire Indonesian nation in the organization of housing or a decent place to live. Nowadays, many people find it difficult or even unable to fulfill the needs of a livable residence due to their low income. This problem is then accommodated by Article 15 paragraph (1) of Law No. 20/2011 which stipulates that the government is responsible for the construction of public flats. One of the public flats in Indonesia is Rumah Susun Sederhana Sewa (Rusunawa), which is a flat with rental status and built using State Budget (APBN) and / or Regional Budget (APBD) funds with its main function as housing. Basically, the ownership of the Rusunawa unit is based on the Building Ownership Certificate (SKBG), which is a proof of ownership of a flat unit on state or regional property in the form of land or waqf land by way of rent. This means that the owner of the Rusunawa unit doesn’t have property rights, but only has the right to rent for a certain period of time in accordance with the agreement. Thus, Rusunawa should not be traded carelessly, but the fact is that Rusunawa is often traded by certain individuals and even this practice is also supported by policy makers. The purpose of writing in this study is to determine the legal validity of the practice of buying and selling Rusunawa and what legal liability can be carried out against the practice of buying and selling Rusunawa.